Chemically synthesized peptides predicted from the nucleotide sequence of the hepatitis B virus genome elicit antibodies reactive with the native envelope protein of Dane particles. - Lerner, R A (1981)
Thirteen peptides corresponding to amino acid sequences predicted from the nucleotide sequence of the hepatitis B surface antigen were synthesized chemically. The free or carrier-linked synthetic peptides were injected into rabbits, and 7 of the 13 elicited an antipeptide response. Antisera against four of the six soluble peptides longer than 10 amino acids were reactive with native antigen and specifically precipitated the 23,000- and 28,000-dalton forms from Dane particles. As the hepatitis molecule had not been chosen for study because of any structural feature suggesting unique opportunities for success, these results suggest that the strategy is general and should work for any protein as long as enough domains are studied. Peptides such as these could prove to be ideal vaccines.